Crystal structure of N-ethyl-4-[3-(trifluoromethyl)-phenyl]piperazine-1-carbothioamide, C14H18F3N3S - Al-Wahaibi, Lamya H.; Blacque, Olivier; Al-Shaalan, Nora H.; Tiekink, Edward R. T. *; El-Emam, Ali A. (De Gruyter, 2023)
C14H18F3N3S, monoclinic, P21/c (no. 14), a = 4.61919(4) Å, b = 29.1507(3) Å, c = 11.27803(10) Å, β = 94.4768(8)°, V = 1513.99(3) Å3, Z = 4, R gt (F) = 0.0588, wR ref (F 2) = 0.1579, T = 160 K.